2022
DOI: 10.1038/s41591-022-01919-8
|View full text |Cite|
|
Sign up to set email alerts
|

Pepinemab antibody blockade of SEMA4D in early Huntington’s disease: a randomized, placebo-controlled, phase 2 trial

Abstract: SIGNAL is a multicenter, randomized, double-blind, placebo-controlled phase 2 study (no. NCT02481674) established to evaluate pepinemab, a semaphorin 4D (SEMA4D)-blocking antibody, for treatment of Huntington’s disease (HD). The trial enrolled a total of 265 HD gene expansion carriers with either early manifest (EM, n = 179) or late prodromal (LP, n = 86) HD, randomized (1:1) to receive 18 monthly infusions of pepinemab (n = 91 EM, 41 LP) or placebo (n = 88 EM, 45 LP). Pepinemab was generally well tolerated, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…39,40 Indeed, SEMA4D plays a critical role in regulating the transition between homeostatic and reactive states of various types of glial cells. Antibody blockade of SEMA4D is being explored as a potential disease modifying strategy to slow cognitive decline in patients with early Huntington’s disease 41 and may be beneficial in other ACD. We have also identified a prominent signal near RBFOX1 , a gene that encodes the RNA binding fox-1 which has been shown to have a role in alternative splicing of the amyloid precursor protein.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Indeed, SEMA4D plays a critical role in regulating the transition between homeostatic and reactive states of various types of glial cells. Antibody blockade of SEMA4D is being explored as a potential disease modifying strategy to slow cognitive decline in patients with early Huntington’s disease 41 and may be beneficial in other ACD. We have also identified a prominent signal near RBFOX1 , a gene that encodes the RNA binding fox-1 which has been shown to have a role in alternative splicing of the amyloid precursor protein.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that target these pathogenic processes have the potential to be broadly applicable to multiple devastating neurologic diseases. Clinical evaluation of the safety and efficacy of pepinemab (VX15/2503), a humanized anti-SEMA4D monoclonal antibody, has been initiated, including a completed Phase I trial in patients with multiple sclerosis (NCT01764737) [63], a Phase II trial in Huntington's disease (NCT02481674) that is complete and will be reported elsewhere [64], and an ongoing Phase I/II study of pepinemab in Alzheimer's disease (NCT04381468). Clinical and imaging outcomes including FDG-PET may provide further evidence of the biologic activity of astrocytes and their contribution to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In this edition, we highlight the ongoing PIVOT HD (NCT05358717) [1] and the recently completed SIGNAL (NCT05358717) [2] clinical trials. We tabulate all currently registered and ongoing clinical trials in Tables 2 to 4.…”
Section: Introductionmentioning
confidence: 99%
“…SEMA4D is a protein of the semaphorin family involved in immune regulation [11]. In the brain, it regulates the transition to reactive states in glial cells [2]. Blockade of SEMA4D with immunotherapy improved pathology and clinical phenotypes in the YAC128 mice [12].…”
Section: Introductionmentioning
confidence: 99%